Empowering Children Through Sexual Education: A Community Service Initiative in West Pancoran, South Jakarta - Ilham, Oryzea Sativa; Yuandari, Ni Nyoman Putri Shopia; Hanum, Az Zahra Azizah; Alfarisy, Edon Salman; Budiman, Muhammad Fathar Hamada; Utami, Nanda Putri; Rahim, Noorfi Azizah; Maharani, Silvina Angelia Dwi; Harmasi, Stefan Garnett (Center for Research and Community Service of Sampoerna University, 2025)
Janakara Mengabdi community service initiative conducted from February to May 2024 at SDN 07 and SDN 08 Pancoran Pagi, aimed at introducing age-appropriate sexual education to elementary school students through the development and distribution of the “Jaka & Nara Tumbuh Dewasa” storybook. The program included baseline surveys, interactive storytelling sessions, and both physical and digital book distribution. Results indicated a high completion rate of planned activities and positive engagement from students. The baseline data reinforced the need for early education on personal boundaries and body awareness, aligning with current research that shows significant increases in children's knowledge following structured educational interventions. Although the program demonstrated initial success, further steps such as ISBN registration and a sustainability plan for the storybook’s future use remain areas for development. The findings emphasize the role of creative educational tools in empowering children, preventing abuse, and fostering community awareness around child safety and health development.